Sisters' fate - Spotswood, Jessica (Cahill Witch chronicles, 2015)
"The Sisters and the Brotherhood enter a near all-out war as an epidemic breaks out in New London, and the prophecy that one sister will murder another comes ever closer to fruition"--Provided by publisher.